LBES/STATCOM for Power Quality Improvement in a Grid connected Wind Power System - Dr.R.Srinivasa Rao, T Krishna Mohan, P Lakshmi Narayana (International Journal of Scientific Research and Management (IJSRM), 2014)
India, over the years, has been a trend-setting nation with regard to Wind Power Utilization and decades of concentrated efforts have started to yield gratifying results. Penetrating the wind energy into the grid affects the power quality due to variable wind speed components. The foremost power quality snags are active power, reactive power, voltage sag, voltage swell, flicker, and harmonics. This paper shows the existence of power quality problem due to installation of wind turbine with the grid. A new LEBSSTATCOM scheme for grid connected wind power system has been developed using the MATLAB/SIMULINK to mitigate the power quality problems. In this the STATCOM is inputted by the Lithium-ion Battery energy Storage system it rapidly injects or absorbed reactive power to stabilize the grid system. Finally the results of with Li-STATCOM and without LEBS-STATCOM are compared and a mark reduction in total harmonic reduction is observed.